Analysis of the differences in immune indexes of common gene mutations and 5q- chromosome karyotype mutations in MDS - Hanxue Zheng; Zilu Meng; Liansheng Zhang; Lijuan Li (Discover Oncology)
Abstract Objective This study aims to investigate the interaction between common gene and 5q- chromosome karyotype mutations and the immune microenvironment in myelodysplastic syndromes (MDS), and explore the potential prognostic value of immune markers in MDS. Methods A total of 83 MDS patients treated at the Second Hospital of Lanzhou University between January 2019 and April 2024 were enrolled in this study. Patients were divided into mutation and wild-type groups based on gene mutations and the presence of 5q- chromosomal abnormalities. Co-mutations in MDS patients were analyzed. A total of 19 fine immune parameters were measured in the samples using flow cytometry and flow cytometric bead array (CBA) technology. Changes in immune markers between the mutation and wild-type groups were observed, and the correlation between lymphocyte subsets and cytokines in the mutation group was analyzed. Results Significant differences in immune markers were observed between the common gene mutation group and the wild-type group in MDS (P < 0.05). Correlations between lymphocyte subsets and cytokines were identified in ASXL1, RUNX1, SF3B1, TET2, TP53, U2AF1, and 5q- mutation groups. Conclusion This study investigates the correlation between common MDS mutations and cytokine/lymphocyte subpopulations, preliminarily revealing the interaction between genetic factors and immune markers in myelodysplastic syndrome (MDS), and emphasizes the potential important role of the Th17/Treg axis in the tumor immune microenvironment of MDS, but does not verify the mechanism. The study suggests that fine immune parameters have potential prognostic value in MDS and may guide future MDS treatment strategies.